Seed biology of Australian arid zone species: Germination of 18 species used for rehabilitation - Commander, L.; Merritt, D.; Rokich, D.; Dixon, Kingsley (Elsevier, 2009)
Revegetation of disturbed land, particularly in arid environments, is often hindered by low seedling establishment. Information on seed biology and germination cues of keystone species is lacking, particularly in arid Australia; a major zone for mining developments. This study investigated seed characteristics and germination of 18 common species required for rehabilitation of disturbed areas at Shark Bay Salt in the Shark Bay World Heritage Area, Western Australia. Untreated seeds of seven species (Aphanopetalum clematideum, Atriplex bunburyana, Austrostipa elegantissima, Melaleuca cardiophylla, Pembertonia latisquamea, Rhagodia baccata, Salsola tragus) exhibited high germination percentages. Seeds of two species (Acacia tetragonophylla, Stylobasium spathulatum) had low imbibition, which increased with hot-water treatment, hence require scarification for germination. Gibberellic acid, smoke water and karrikinolide (a butenolide isolated from smoke) substantially increased germination percentages of three species (Anthocercis littorea, Diplolaena grandiflora, Solanum orbiculatum). Seeds of the remaining six species (Dioscorea hastifolia, Eremophila oldfieldii, Nitraria billardierei, Ptilotus exaltatus, Thryptomene baeckeacea, Zygophyllum fruticulosum) had low germination percentages regardless of treatment. Most species germinated equally well at 26/13 °C and 33/18 °C, however seven species had improved performance at 26/13 °C. This study is significant to land managers and conservation agencies with an interest in optimising germination of arid zone seeds for restoration. Crown Copyright © 2009.